Avaliação de desempenho de uma planta microgeradora de energia elétrica a partir do biogás - Siebert, Cristela Marta (2021)
There is an annual growth of the number of micro power plants installed in Brazil, especially after the implementation of the regulation 482/2012, that regulates the generation distributed in Brazil. Small farm plants producing electricity from biogas belong to this group and share part of this growth. These plants are composed of biodigester for the production of biogas and generator for conversion of biogas into electric energy. The operation cost and investment are high, and the maximum efficiency of the process should be desired for better financial return. In the western region of the State of Paraná, Brazil, there are different biogas plant sets, but few publications about their efficiency. With the aim of measure de efficiency of a micro power plant from biogas, it was realized the energy balance of a micro power plant located on the city of Toledo, Paraná. The goal of this paper was to contribute with the best sets recognition for each location and purpose. The plant analyzed has two biodigesters, low-tech for biogas production, and an Otto engine and generator for conversion into electricity. The results shows that the biodigesters consume 65% of the volatile solids present in the substrate producing biogas with a methane concentration of 57% on average. The generator engine set achieves 23,8% efficiency, operating at 70 kWh with electricity injection into the utility distribution network. The equipment needed for the operation of the system consumes 19,46% of the energy produced, most of which is used in the transport of substrates. The energy balance of the plant indicates a performance of 27,24% in energy use.